(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study evaluated improvements in preoperative and postoperative nutritional status in infants with severe Pierre Robin Sequence (PRS) undergoing mandibular distraction osteogenesis (MDO). Methods: A prospective, uncontrolled clinical interventional study was conducted on 102 severe PRS patients who underwent bilateral MDO at the Craniofacial and Plastic Surgery Department, Vietnam National Children’s Hospital, from 2019 to 2023. Results: Among the patients, 35.3% had inflammation, and 55.9% were malnourished. All required preoperative nutritional support. By the end of the activation phase, 82.4% could feed orally, and by three months postoperatively, all achieved normal feeding ability. Average birth weight was 2,917.65 ± 592.62 grams, increasing to 3,496.14 ± 1,008.43 grams at surgery. After device removal, weight rose to 4,650.23 ± 1,017.5 grams (159.4% increase from birth weight), reaching 8,450.3 ± 1,147.1 grams at nine months (289.68% increase). These results indicate significant improvements in nutritional status and weight gain comparable to healthy infants. Conclusion: MDO is a safe, effective, and feasible procedure that significantly enhances the physical condition and nutritional status of infants with severe PRS.